Pengaruh Teknik Relaksasi Benson Terhadap Intensitas Nyeri Pada Pasien Pasca Operasi Seksio Sesarea Di Rumah Sakit Umum Puri Raharja Denpasar - Gusti Ayu Putu Jayanti; I Gusti Ayu Ratih Agustini; Ni Komang Purwaningsih (Poltekkes Kemenkes Malang, 2020)
Caesarean section is a surgical procedure to give birth which is done by doing incision in the abdominal wall of the mother. Pain that is felt by mothers after cesarean section comes from wounds found in the stomach. One of the therapies used to reduce pain is the Bensons relaxation technique. The purpose of this study was to determine the effect of Benson s relaxation technique on pain intensity in postoperative patients with caesarean section at Puri Raharja General Hospital Denpasar. The design of this study was a pre experimental design with a total sample was 15 respondents. The sampling technique used was nonprobability sampling, namely purposive sampling to determine whether there was a significant correlation between the independent and the dependent variable used the Wilcoxon test. P value is 0,000, therefore it can be concluded that Benson s relaxation technique significantly influenced pain intensity in postoperative cesarean section patients. The results of this study can be used by families and nurses to implement Benson s relaxation in order to reduce the pain intensity of patients post cesarean section surgery at the Hospital.